FAKTOR KUALITAS HIDUP PASIEN KANKER - Prasetyo, Doddy Yumam; Suprayitno, Edy (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Chemotherapy is one of therapies to cancer in an effort tocure it. Chemotherapy has psychological and fisiological side effets such as changes in self-esteem, sexuality, well-being, skin damage, nausea and vomiting. The focus to be considered in the patients of cancer atundergoing chemotherapy is to improve the quality of life. A good quality of life is very important so that patients can improve their stated of good health and as additional information in evaluating the outcome of treatment. Objective : to determine factors that affect quality of life in patients of cancer undergoin chemotherapy. Methods : this research is a descriptive analytic study with accidental sampling approach of 30 respondent fot 1 month. Instrument used was SF-36 questionnaire and analyzed using chi square test. Result : the result showed that age, sex, maital stated, occupation, education level, body mass index, cacer stage and family support had no effect on quality of live in cancer respondent at Pku Muhammadiyah Yogyakarta hospital with p 0,05. Conclution and suggestion : there are not factors that affect for qualityof live in cancer patients undergoing chemotherapy. This research needs to be developed to determine need for supportive care and its relationship with quality of life.